1994
DOI: 10.2172/10182632
|View full text |Cite
|
Sign up to set email alerts
|

Uranium hexafluoride public risk

Abstract: The limiting value for uranium toxicity in a humanbeing should be based on the concentration of uranium (U) in the kidneys. The threshold for nephrotoxicity appears to lie very near 3 Pg U per gram kidney tissue. There does not appear to be strong scientific support for any other improved estimate, either higher or lower than this, of the threshold for uranium nephrotoxicity in a humanbeing. The value 3 Pg U per gram kidney is the concentration that results from a single intake of about 30 mg soluble uranium b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…This is consistent with Fisher et al (1994) who concluded that the "age of the subject was not an important factor in assessing the consequences factor of airborne uranium" and that the extant standards were adequate to protect children and the fetus (Fisher et al 1994). …”
Section: Applicability To Child and Fetussupporting
confidence: 83%
See 2 more Smart Citations
“…This is consistent with Fisher et al (1994) who concluded that the "age of the subject was not an important factor in assessing the consequences factor of airborne uranium" and that the extant standards were adequate to protect children and the fetus (Fisher et al 1994). …”
Section: Applicability To Child and Fetussupporting
confidence: 83%
“…It is well established that the kidney is the most sensitive organ to toxic effects from uranium; although some have suggested a lower threshold, there is general consensus in the scientific community that a concentration of 3 g of uranium per gram of kidney is the level at which nephrotoxic effects may begin to appear (Alexander 1984;ATSDR 1999;Bailey and Davis 2002;Brodsky 1996;Fisher et al 1994;Fulco et al 2000;Kathren and Weber 1988;Leggett 1989;Spoor and Hursh 1973;Stannard 1988). At kidney concentrations Ͻ3 g of uranium per gram, there would be no observable clinical effects; at this level, for conservatism mild transitory wholly reversible kidney effects are assumed based on the appearance of various biomarkers in urine that are indicative of kidney damage including glucosuria, albuminuria, and elevated ␤-2 microglobulin and blood creatinine levels.…”
Section: Establishment Of Level For Mild Transient Health Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Species Endpoint Effect concentration Diamond et al (1989) rat (Long Evans) LOEC for renal function 0.7 Fisher et al (1994cited by Hartmann et al, 2000 humans threshold for kidney toxicity 3 Gilman et al (1998a,c) rabbitsdmale and female New Zealand white LOEC for histopathological changes 0.04 Gilman et al (1998b) ratsdSprague-Dawley LOEC for renal damage 0.2 Gilman et al (1998c) rabbitsdmale New Zealand white LOEC for renal damage 0.18 Morrow et al (1982) Beagle dogs renal injury threshold 0.3 Zhao and Zhao (1990) humans LOEC for kidney function 2.6 be reparable, and may be ecologically irrelevant because the kidney often has excess or redundant capacity. Nonetheless, renal damage may render the organism more susceptible to other environmental stressors, and so could well have indirect ecological consequences.…”
Section: Authorsmentioning
confidence: 99%